ANALISIS PENGARUH BOPO, LDR, NPL, SIZE, CAR DAN NIM TERHADAP ROA (Studi pada Bank Umum Konvensional Yang Listing di Bursa Efek Indonesia Periode 2009-2013) - Yatiningsih, Nur Fakhri; Chabachib, Mochammad (Faculty of Economics and Business Diponegoro University, 2015)
Financial performance has become one of the considerations about the condition of a bank. Many factors affect the financial performance of a bank. Therefore, this study examines the effect of Operating Expenses Operating Income (ROA), Loan to Deposit Ratio (LDR), Non Performing Loan (NPL), SIZE, Capital Adequacy Ratio (CAR) and Net Interest Margin (NIM) of the Return On Asset ( ROA) in conventional commercial banks in Indonesia 2009-2013.The sample used in this study consists of 21 conventional commercial banks listed on the Indonesian Stock Exchange (BEI) 2009-2013. This study used the purposive sampling method. Data obtained from the Indonesian Capital Market Directory (ICMD) and Annual Report. Data analysis method used is multiple linear regression analysis which is previously performed classical assumption, such as normality test, multicollinearity test, autocorrelation test, and heteroskedastisitas test. Hypothesis testing by using the F test and t test. The Results from this study indicates that BOPO , NPL , LDR and CAR significant negative effect on ROA . SIZE and NIM significant positive effect on ROA . The amount of determination degree test (Adjusted R Square ) is equal to 0.784 , that means the independent variable such as ROA, LDR , NPL , SIZE , CAR and NIM have the impact on ROA of 78.4 % . Meanwhile , the remaining 21.5 % is explained by other variables outside the model of this study .